2018
DOI: 10.1016/j.anaerobe.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative, quantitative and genotypic evaluation of Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum isolated from individuals with different periodontal clinical conditions

Abstract: Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum are strongly associated with periodontitis, and their evaluations are relevant to understand their role in the etiology and progression of periodontal diseases. In this study, the qualitative and quantitative detection of A. actinomycetemcomitans and F. nucleatum, as well as their genetic diversity, were evaluated in individuals with gingivitis, chronic periodontitis and periodontally healthy. In addition, the biotyping, serotyping, and prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 56 publications
1
24
0
3
Order By: Relevance
“…F. nucleatum is an important microorganism in the development of dental biofilms; it can adhere to most plaque bacteria and is involved in linking early and late migratory microorganisms [27]. In a previous study, Arenas Rodrigues et al [28] isolated F. nucleatum from individuals with both healthy periodontal status and periodontal disease, and Zhou et al [29] found that 58.5% of healthy young adults were positive for this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…F. nucleatum is an important microorganism in the development of dental biofilms; it can adhere to most plaque bacteria and is involved in linking early and late migratory microorganisms [27]. In a previous study, Arenas Rodrigues et al [28] isolated F. nucleatum from individuals with both healthy periodontal status and periodontal disease, and Zhou et al [29] found that 58.5% of healthy young adults were positive for this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, periodontal sites harboring Aggregatibacter actinomycetemcomitans demonstrate deeper probing depths (PDs) with or without clinical signs of inflammation. 12 Research suggests that a significant correlation exists in the overall periodontal conditions with the soft tissue conditions around dental implants that indicates a possible spread of infection from periodontally compromised/untreated sites to the peri-implant sulci. 13,14 To date, no comparison of clinical, radiographic, and implant survival rates of SDIs has been provided in a group of treated GAgP patients and periodontally healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Aa is a periodontal pathogen associated with severe forms of periodontitis, [117][118][119][120][121] both localized aggressive periodontitis (LAP) and chronic periodontitis. 117,118,[122][123][124][125][126][127][128][129][130][131] In contrast to other oral bacteria, Aa has a unique capacity to induce neutrophil hypercitrullination, suggesting a potential role of this bacterium in generating the periodontal citrullinome. 72 Similar to host-immune pore-forming pathways, Aa hyperactivates PADs by inducing membranolytic damage on neutrophils.…”
Section: Fert-bober Et Almentioning
confidence: 99%